Pendidikan Kewirausahaan di Pesantren Sebagai Upaya dalam Membangun Semangat Para Santri untuk Berwirausaha - Khotibul Umam (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2016)
Entrepreneurship education is one of the media in introducing the business world while motivating the students to be entrepreneur. As an educational institution that is rooted in the society, the existence of islamic boarding house has significance in solving the problems of the society’s economy, especially in the problems of unemployment and poverty. The presence of entrepreneurship education in the islamic boarding house is expected to build interest in the students motivation to become success entrepreneur where the students of islamic boarding house not only have the ability affective and cognitive in the field of religious studies, but also have psychomotor abilities in the world of work as well as creating their own businesses after they finish their education at islamic boarding house as a solution in reducing the unemployment rate which will prosper and build the economy of surrounding societies.